(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
The treatment of patients with cleft lip and palate is a complicated medical-social problem. The residual and secondary deformations of the nose, upper lip, and dentoalveolar require surgical correction in these patients after undergoing complete reconstruction as a child.